Microstructure of rapidly solidified foils of alloys of the bismuth – tin system - Shepelevich, Vasiliy G.; Shcherbachenko, Liliya P. (Journal of the Belarusian State University. Physics, 2019)
It is established that in the rapid-quenched foils of the bismuth-tin alloys the volume fraction of the phases does not depend on the distance to their outer surface, which indicates a homogeneous distribution of phases in the volume of the foil. The formation of a dispersed structure in foils of a eutectic composition is caused by the action of the spinodal decomposition of a supersaturated liquid solution that promotes a homogeneous distribution of the nuclei of the crystalline phases, the independence of the mean chord lengths of random secants on the phase sections and the specific surface of the interface from the distance to the foil surface. The dependence of the average lengths of the chords of random secants on the phase sections and the specific surface of the interface from the distance to the surface of the foil of alloys, whose composition differs significantly from the eutectic, is due to a decrease in the supercooling of the melt as the crystallization front moves.